Housebuilding for children - Walker, Les. (Woodstock, N.Y. : Overlook Press, 1977)
Step-by-step illustrated instructions for building six different houses with a description of the necessary tools and equipment.
Keywords: House construction -- Juvenile literature; House construction; Handicraft; House construction; Building; House construction; Handicraft -- Housebuilding